Rancang Bangun Motion Graphic Biografi Prof. Ganefri, Ph.D sebagai Tokoh dalam Dunia Pendidikan - Widya Falisya; Wiki Lofandri (Lembaga Yasin AlSys, 2026)
Changes in the information consumption patterns of younger generations have driven the need for biographical media on educational figures that are more visual, concise, and communicative. This study aimed to design and develop a motion graphic biography of Prof. Ganefri, Ph.D. as a medium for figure literacy and character education for school and university students. The study employed a research and development method by adapting the seven stages of Borg and Gall, namely the identification of potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. Data were collected through documentation studies, direct interviews, observation of visual references, expert validation, and user questionnaires, and were then analyzed descriptively and quantitatively. The result of the study was a motion graphic video with a duration of 2 minutes 52 seconds, Full HD resolution of 1920 × 1080 pixels, a speed of 60 frames per second, and MP4 H.264 format. The product combined semi-realistic vector illustrations, 2.5D parallax techniques, kinetic typography, voice-over, background music, and sound effects to present the academic and leadership journey of Prof. Ganefri as well as the values of hard work, integrity, responsibility, and dedication. This study expands the use of motion graphics as a medium for biographical literacy on educational figures as well as a means of strengthening character education. Further testing is needed to measure the influence of the media on the audience’s knowledge, motivation, and information retention.